2010
DOI: 10.1007/s10470-010-9505-5
|View full text |Cite
|
Sign up to set email alerts
|

PSPICE modeling of meminductor

Abstract: PSPICE models of current-and flux-controlled meminductor are described. The models consist of two parts, one of which represents the state-space description of the memory effect of the device, and the other part is an inductor whose inductance depends on the system state. The basic fingerprints of the meminductor, i.e. the fluxcurrent pinched hysteresis loops, the unambiguous constitutive relation between the time integral of flux and electric charge, and identical zero-crossing points of flux and current wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Let us consider an FC meminductor with the constitutive relation q=0.001ρ+350ρ3where the symbols q and ρ denote the charge and the time‐domain integral of flux (TIF), respectively . Then, the SE and the PE of the meminductor are as follows: dx1/dt=v,dx2/dt=x1,i=ΛMx1=0.001+1050x22x1where state variable x 1 is the flux φ , state variable x 2 is ρ (TIF) and Λ M denotes the inverse meminductance obtained from Equation as a derivative of charge with respect to TIF.…”
Section: Example Of Meminductor Emulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us consider an FC meminductor with the constitutive relation q=0.001ρ+350ρ3where the symbols q and ρ denote the charge and the time‐domain integral of flux (TIF), respectively . Then, the SE and the PE of the meminductor are as follows: dx1/dt=v,dx2/dt=x1,i=ΛMx1=0.001+1050x22x1where state variable x 1 is the flux φ , state variable x 2 is ρ (TIF) and Λ M denotes the inverse meminductance obtained from Equation as a derivative of charge with respect to TIF.…”
Section: Example Of Meminductor Emulationmentioning
confidence: 99%
“…Let us consider an FC meminductor with the constitutive relation q ¼ 0:001 r þ 350 r 3 (5) where the symbols q and r denote the charge and the time-domain integral of flux (TIF), respectively [10]. Then, the SE and the PE of the meminductor are as follows:…”
Section: Example Of Meminductor Emulationmentioning
confidence: 99%
“…Our approach, therefore, significantly improves simulation robustness in terms of convergence and overflows for i charge and i discharge . Note that the modeling approach herein can be extended to memcapacitor and meminductor [8] modeling along similar lines to Biolek et al [32].…”
Section: B Proposed Model For Memristor Dynamic Behaviormentioning
confidence: 96%
“…But, the first theoretical meminductor model is build by Biolek et al based on the idea of a simple electromechanical system [5], shown in Fig. 8.2.…”
Section: −1 T T O ϕ(τ )Dτ ϕ(T) (84)mentioning
confidence: 99%